Medical Dispute Resolution Between Dentists and Patients Through Mediation Mechanisms - Syafri, Deni; Efrila, Efrila; Prasetyo, Boedi (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
Medical disputes between dentists and patients often arise due to negligence in medical treatment. This study aims to conduct a further analysis of the resolution of medical disputes between dentists and patients. This research is classified as normative juridical research using a statutory approach and legal concept analysis. The data collection technique was carried out through a literature review. The results of the study indicate that medical dispute resolution can be conducted through mediation, either through arbitration bodies, the Indonesian Medical Discipline Honorary Council (MKDKI), or the Indonesian Dental Association (IDI) as a professional organization of dentists that has the authority to act as a mediator. Through mediation, disputes are expected to be resolved fairly and efficiently without going through lengthy legal proceedings that may potentially disadvantage one of the parties. In conclusion, the resolution of medical disputes between dentists and patients should prioritize mediation efforts in order to achieve a satisfactory settlement for both parties.